The revival of labor liberalism - Battista, Andrew (University of Illinois Press, 2008)
Revival of Labor Liberalism is a careful analysis of the twentieth-century decline of unions and liberals and the important efforts to revive their political fortunes. The break in the labor-liberal coalition in the late 1960s paved the way for an ascendant Republican Party and linked business and conservative interests bent on revising earlier policies implemented by the New Deal and the Great Society. Divided by politics and new social movements in the late 1960s, unions and liberals united in several new political organizations between the mid-1970s and mid-1980s in order to rebuild their coalition and its influence. This is the first book to chronicle the efforts of these organizations, which include the Progressive Alliance, Citizen Labor Energy Coalition, and National Labor Committee. Drawing from extensive documentary research and in-depth interviews with union leaders and political activists, Andrew Battista argues that these new organizations made limited but real progress in reconstructing and strengthening the labor-liberal coalition. He also shows that their restorative efforts were closely tied to factional conflicts in the labor movement. Although the labor-liberal alliance remains far weaker than the rival business-conservative alliance, Battista emphasizes its crucial role in labor and political history since 1968. In focusing on this evolving partnership, this study provides a broad analysis of factional divisions among both unions and liberals and considers the future of unionism and the labor-liberal coalition in America.
Keywords: Labor unions -- Political activity -- United States -- History.; Liberalism -- United States -- History.; United States -- Politics and government -- 20th century.; Working class -- Political activity -- United States.; Progressivism (United States politics); Syndicats -- Activité politique -- États-Unis -- Histoire.; Libéralisme -- États-Unis -- Histoire.; États-Unis -- Politique et gouvernement -- 20e siècle.; Travailleurs -- Activité politique -- États-Unis.; Progressisme -- États-Unis.; HISTORY / General; Labor unions -- Political activity; Liberalism; Politics and government; Working class -- Political activity; United States; Gewerkschaft; Liberalismus; USA; 1900-1999; Electronic books.; History